2009
DOI: 10.4251/wjgo.v1.i1.82
|View full text |Cite
|
Sign up to set email alerts
|

Studies on activity of various extracts of Mentha arvensis Linn against drug induced gastric ulcer in mammals

Abstract: AIM:To examine the antiulcerogenic effects of various extracts of Mentha arvensis Linn on acid, ethanol and pylorus ligated ulcer models in rats and mice. METHODS:Various crude extracts of petroleum ether, chloroform, or aqueous at a dose of 2 g/kg po did not produce any signs or symptoms of toxicity in treated animals. In the pyloric ligation model oral administration of different extracts such as petroleum ether, chloroform and aqueous at 375 mg/kg po , standard drug ranitidine 60 mg/kg po and control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…f Previously reported by Oinonen et al (2006), Kapp (2015) and Londonkar and Poddar (2009) in M. arvensis.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 87%
“…f Previously reported by Oinonen et al (2006), Kapp (2015) and Londonkar and Poddar (2009) in M. arvensis.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 87%
“…Other than that, flavonoids have been shown to scavenge free radicals (Londonkar & Poddar, 2009) and could be responsible for the recent report on the antioxidant activity of CEBP (Zakaria et al, 2011). This is further supported by Shetty et al (2008) who discussed that flavonoids could possibly inhibit the gastric mucosal injury by scavenging the ethanol-and indomethacin-generated oxygen metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…hydroperoxy and superoxide anion free radicals) resulting from the metabolism of ethanol and these ROS will take part in the mechanism of acute and chronic ulceration in the gastric mucosa. Several studies have reported that ROS and lipid peroxidation will initially attack and damage many biological molecules (e.g., prostaglandins) followed by a continuing chain of reactions that will lead to cell injury and ultimately cell death (Londonkar & Poddar, 2009). The ability of CEBP to reduce ethanol-induced gastric ulcer in the present study suggests the involvement of its cytoprotective effect, which could be associated with the antioxidant and free radical scavenging effects of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Being a hybrid, it is usually sterile, producing no seeds and reproducing only vegetatively, spreading by its rhizomes. Scientific studies have shown that the petroleum ether, chloroform, or aqueous extract (375 mg kg À1 oral) was effective in preventing ibuprofen plus pyloric ligation-, 0.6 mol l À1 HCl-, and 90% ethanol-induced gastric ulcerations in rats (Londonkar and Poddar, 2009). It prevents smooth muscle contractions and can be used for relief from abdominal pain associated with irritable bowel syndrome.…”
Section: Mentha Arvensismentioning
confidence: 99%